The Servicescape Strives for Community Lodge Personal Branding Through Competitive Advantage in Hospitality Industry - Wilma Cordelia Izaak; Amalya Diva Andriyani (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2025)
This study explores the role of Servicescape on personal branding and the competitive advantage of local community lodges in Indonesia’s growing tourism industry. Local community lodges offer authentic cultural experiences and are increasingly sought after by tourists. However, these lodges have some issues with organizational management, which are limited to traditional management techniques and need to promote their services. The study was conducted in Sawiran Community Lodge in Malang, East Java, which has faced problems with ineffective management and the non-implementation of standard operating procedures. The study utilizes a mixed-method approach, including direct observation, questionnaires, in-depth interviews, and purposive sampling with 148 associates of the community lodge. The research reveals that a well-designed Servicescape influences the physical, social, and digital environment and positively impacts the lodges’ competitive advantage and personal branding. The findings suggest that by improving the Servicescape and adhering to standardized operating procedures (SOPs), local community lodges can enhance personal branding mediated by competitive advantages (e.g., guest experience, differentiation from competitors, healthy occupancy rate, and fostering a strong sense of pride among employees). This, in turn, can lead to increased income and a more sustainable tourism model, benefiting both residents and visitors. The research underscores the need for community lodges to adapt to modern practices such as digital marketing, customer relationship management, and sustainable operations to maintain relevance and appeal in a competitive market.